Shatter the sky - Wells, Rebecca Kim (Simon & Schuster Books for Young Readers, 2019)
Maren, desperate to save her kidnapped girlfriend, plans to steal one of the emperor's dragons and storm the Aurati stronghold, but her success depends on becoming an apprentice to the emperor's mysterious dragon trainer, which proves to be a dangerous venture.